The Construction Identity of “Jogja Noise Bombing” Music Community in Yogyakarta - Muhammad Adnan Firdaus; Fajar Junaedi (Jogjakarta Communication Conference (JCC), 2025)
Music that is often listened to by many people generally has tonal harmony and is comfortable to listen to. However, there are some types of music that do not prioritize tonal harmony, one of which is noise music. Jogja Noise Bombing (JNB) is one of the noise music communities that developed in Yogyakarta. This community is a forum for noise music players in this city and is known for its experimental musical approach, using loud noises, ambient sounds, drones, circuit bending, and homemade synthesizers. Apart from being a space for self-actualization, JNB also plays a role in shaping and projecting a unique collective identity for its members. This research aims to understand how the identity construction of Jogja Noise Bombing community is formed through noise music and social dynamics within the community. Using a qualitative method with a constructivist paradigm and a phenomenological approach, this research involves observation, in-depth interviews with community members, as well as social media analysis and performance documentation. The results show that JNB's identity is formed through the merging of local elements of Yogyakarta with the global spirit of the noise movement. This research is expected to enrich the study of experimental music in Indonesia and open wider discussions about the relationship between music, identity and alternative culture.